Synthesis and electronic properties of comb-like polyamides bearing different contents of tetraaniline pendant groups. Issue 56 (24th May 2016) - Yin, Mingying; Yan, Ying; Li, Fangfei; Liu, Xincai; Wang, Ce; Chao, Danming
Abstract : Tunable electronic properties could be accomplished by importing different numbers of tetraaniline pendants into the polymeric scaffolds. Abstract : Comb-like polyamides bearing different contents of tetraaniline pendant groups were synthesized via nucleophilic polymerization coupled with a post-functionalization method, and exhibit excellent solubility, good thermal stability and interesting spectroscopic properties. Their electronic properties, including conductivity, dielectricity, electroactivity, electrochromism and anticorrosion, were effectively adjusted and controlled by importing different numbers of tetraaniline pendant groups.